Conservation of DNA and ligand binding properties of retinoid X receptor from the placozoan Trichoplax adhaerens to human. Issue 184 (November 2018) - Reitzel, Adam M.; Macrander, Jason; Mane-Padros, Daniel; Fang, Bin; Sladek, Frances M.; Tarrant, Ann M.
Graphical abstract: Abstract: Nuclear receptors are a superfamily of transcription factors restricted to animals. These transcription factors regulate a wide variety of genes with diverse roles in cellular homeostasis, development, and physiology. The origin and specificity of ligand binding within lineages of nuclear receptors ( e.g ., subfamilies) continues to be a focus of investigation geared toward understanding how the functions of these proteins were shaped over evolutionary history. Among early-diverging animal lineages, the retinoid X receptor (RXR) is first detected in the placozoan, Trichoplax adhaerens. To gain insight into RXR evolution, we characterized ligand- and DNA-binding activity of the RXR from T. adhaerens (TaRXR). Like bilaterian RXRs, TaRXR specifically bound 9- cis -retinoic acid, which is consistent with a recently published result and supports a conclusion that the ancestral RXR bound ligand. DNA binding site specificity of TaRXR was determined through protein binding microarrays (PBMs) and compared with human RXRɑ. The binding sites for these two RXR proteins were broadly conserved (∼85% shared high-affinity sequences within a targeted array), suggesting evolutionary constraint for the regulation of downstream genes. We searched for predicted binding motifs of the T. adhaerens genome within 1000 bases of annotated genes to identify potential regulatory targets. We identified 648 unique protein coding regions with predicted TaRXR binding sites that had diverse predicted functions, with enriched processes related to intracellular signal transduction and protein transport. Together, our data support hypotheses that the original RXR protein in animals bound a ligand with structural similarity to 9- cis -retinoic acid; the DNA motif recognized by RXR has changed little in more than 1 billion years of evolution; and the suite of processes regulated by this transcription factor diversified early in animal evolution.